The Problematic Nature of Execution by Lethal Injection in the United States and People’s Republic of China - Fanucchi, Franchesca (2020)
The United States and the People’s Republic of China perceive the death penalty as a fundamental feature of the criminal justice system. Lethal injection procedures provide these countries with the humane disguise necessary to preserve capital punishment in an environment of evolving societal standards. However, this essay examines the highly problematic nature of execution by lethal injection due to numerous medical, procedural, and bureaucratic concerns often concealed from the public and press. The low-visibility nature of lethal injection in the United States and China has become troublesome, especially since it prevents public, academic, and medical evaluation on the procedure's humaneness and legality (Garland, 2007). To diminish the problems associated with lethal injection, the procedure needs to be administered in a formally regulated and professional manner